The good, the bad and the gory a study on the perception of 4th year journalism students of the University of the Philippines Baguio about the Front page gory photographs of the Philippine Daily Inquirer - Angeles, Aubrey M.; Buccat, Rozzanne Victoria G. (2008)
As society, technology and people's perspectives undergo changes, so does the press. Roughly a decade ago, the gory photographs published on the Philippine Daily Inquirer front page have received numerous criticisms from its readers. With the aid of the Narrative theory, Gerbner General Model and the Hypodermic Needle theory, the Focus Group Discussion and surveys conducted showed that the new breed of potential journalists, the BA Communication students of the University of the Philippines Baguio taking up journalism as either a major or a minor believe that a change is in order. With their knowledge and with highest regard for the public's right to know, these potential journalists deem the publication of gory photographs acceptable -- Author's abstract.